RESPONSIVENESS MARKETING SALES TO CUSTOMER SATISFACTION - Akello Kayode Adeyemi (PT. Berkah Digital Teknologi, 2022)
Purpose of the study —This study aims to examine the effect of marketing responsiveness on customer satisfaction. Research method— Descriptive quantitative research type, the study was conducted by survey method by distributing questionnaires to 100 customers who visited during this research took place at automotive store. Result— The results of research on marketing responsiveness, show that positively significantly influences customer satisfaction. Conclusion— (R Square) of 0.75 or (75%). This shows that the percentage contribution of the influence of the independent variable (responsiveness) to the dependent variable (customer satisfaction) by 75%.